2010
DOI: 10.19030/cier.v3i8.222
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Arabic-Speaking Skill Learning Strategies Among Selected Malay Learners: A Case-Study At The International Islamic University Malaysia (IIUM)

Abstract: In Malaysia, studies have shown that most Malay learners learning Arabic Language exhibit weak Arabic speaking skill despite spending years of learning the language. However, given the same learning environment and experience, some of them could be considered as good Arabic speakers as revealed by the results of Arabic Placement Test conducted by the Center of Languages and pre-Academic Development (CELPAD) of the International Islamic University Malaysia (IIUM). These learners have successfully scored band 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Seker (2016) discovered the potential and significance of SRL research for the foreign language teaching discipline in stimulating and supporting SRL implementation in language instruction. Moreover, Haron, Ahmad, Mamat, and Mohamed (2010) reported in their study that the good Arabic speakers are more frequently apply self-regulated learning strategies. Kosnin (2007) high frequency of help-seeking strategy usage among Arabic learners in Malaysian public universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Seker (2016) discovered the potential and significance of SRL research for the foreign language teaching discipline in stimulating and supporting SRL implementation in language instruction. Moreover, Haron, Ahmad, Mamat, and Mohamed (2010) reported in their study that the good Arabic speakers are more frequently apply self-regulated learning strategies. Kosnin (2007) high frequency of help-seeking strategy usage among Arabic learners in Malaysian public universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several empirical studies Ghani et al, 2011;Awang, Mohamed & Sulaiman, 2013) have concluded that university-level Malay learners are weak in their ability to communicate in the Arabic language. In case to find out the problems may cause students weak in oral speaking, some researchers focus on language learning strategies (Haron et al, 2010;Yusri et al, 2012); some focus on motivation (Ghenghesh, 2010;Bakar, Sulaiman & Rafaai, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it is clear that the language learning environment would significantly cause learners to be weak in Arabic oral speaking. However, some studies found that students could be good Arabic speakers while being in a non-native speaking environment (Haron et al, 2010;Yusri et al, 2012). On the other hand, Haron et al, (2010) argued that the students may lack the strategies required for Arabic language learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching and learning Arabic language in Malaysia is very important particularly for the Muslim Malays in order to perform their prayers and religion [1,2]. According to some researches [3,4,5,6,7] the performance of the students in Arabic language is still very poor.…”
Section: Introductionmentioning
confidence: 99%